2010
DOI: 10.1016/j.bbalip.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Non-mammalian fat-1 gene prevents neoplasia when introduced to a mouse hepatocarcinogenesis model

Abstract: We investigated the effect of a non-mammalian omega-3 desaturase in a mouse hepatocarcinogenesis model. Mice containing double mutations (DM) in c-myc and TGF-α (transforming growth factor-α), leading to liver neoplasia, were crossed with mice containing omega-3 desaturase. MRI analysis of triple mutant (TM) mice showed the absence of neoplasia at all time points for 92% of mice in the study. Pathological changes of TM (TGFα/c-myc/fat-1) mouse liver tissue was similar to control mouse liver tissue. Magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
1
18
1
2
Order By: Relevance
“…Subsequently, several other studies demonstrated decreased liver tumorigenesis in fat-1 mice. In a transgenic hepatoma model containing double mutations in c-myc and TGF- α a constitutive increase in ω -3 PUFA tissue content led to protection from liver tumor development that was associated with a decrease in NF- κ B levels [123]. In the diethylnitrosamine (DEN) model of chemically induced liver carcinogenesis a tumor suppression effect of increased ω -3 PUFA tissue status was demonstrated in the fat-1 mice as well, with lowered plasma TNF- α levels and decreased liver COX-2 expression [31].…”
Section: Beneficial Effects Of ω-3 Pufas In Cancer: Involvement Ofmentioning
confidence: 99%
“…Subsequently, several other studies demonstrated decreased liver tumorigenesis in fat-1 mice. In a transgenic hepatoma model containing double mutations in c-myc and TGF- α a constitutive increase in ω -3 PUFA tissue content led to protection from liver tumor development that was associated with a decrease in NF- κ B levels [123]. In the diethylnitrosamine (DEN) model of chemically induced liver carcinogenesis a tumor suppression effect of increased ω -3 PUFA tissue status was demonstrated in the fat-1 mice as well, with lowered plasma TNF- α levels and decreased liver COX-2 expression [31].…”
Section: Beneficial Effects Of ω-3 Pufas In Cancer: Involvement Ofmentioning
confidence: 99%
“…This resulted in a murine model exhibiting increased levels of n -3 PUFAs with diminished n -6 PUFA concentrations within different organs, including the brain ( 15 ). The Fat-1 mouse was investigated in various disease settings and benefi cial effects of the transgene were reported on liver neoplasia ( 17 ) and atherosclerotic lesions ( 18 ) as well as in the prevention of cerebral seizures induced by pentylenetetrazol ( 19 ). In addition, increased spatial learning performances, enhanced dendritic spine density, and neurogenesis were observed in this model ( 20 ).…”
Section: Lipid Extraction and Gas Chromatographymentioning
confidence: 99%
“…The severe imbalance between n−6 and n−3 fatty acids (n−6/n−3>10) in the modern Western diet and human body tissue has been thought to contribute to today’s increased risk of diseases, including cancer [14], [18]. Evidence from recent studies using the transgenic fat-1 mouse model, which can endogenously convert n−6 to n−3 fatty acids and has a balanced n−6/n−3 ratio in its body tissues [40], strongly supports this notion [41][48]. These studies have demonstrated that decreasing the tissue ratio of n−6/n−3 can significantly reduce the formation and growth of various cancers, which is associated with reduced levels of cancer-related eicosanoids and genes [41][48], suggesting that the tumor - promoting effect of increased D6D activity can be diminished by decreasing tissue n−6/n−3 fatty acid ratio.…”
Section: Discussionmentioning
confidence: 96%